2008
DOI: 10.1029/2008gl035085
|View full text |Cite
|
Sign up to set email alerts
|

Boreal tree pollen sensed by polarization lidar: Depolarizing biogenic chaff

Abstract: [1] Polarization (0.694 mm) lidar measurements show that tree pollen can generate strong laser depolarization in the backscatter from the lower atmosphere. Examples are given illustrating that linear depolarization ratios up to 0.3 are measured in plumes of paper birch pollen at the onset of boreal forest green-out. These pollen are $25 mm in diameter and near-spherical in shape, but with lobes protruding from a surface membrane, which appears to produce the depolarization. Similar lidar findings are frequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 13 publications
1
57
2
Order By: Relevance
“…Previous studies found that depolarization values of 6% typically occur in the upper part of a smoke layer, and comparatively lower depolarization percentages occur below the active layer [50] [52]. Depolarizations of 3% and 5% indicate fresh smoke and smoke layers at higher altitudes, respectively [48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies found that depolarization values of 6% typically occur in the upper part of a smoke layer, and comparatively lower depolarization percentages occur below the active layer [50] [52]. Depolarizations of 3% and 5% indicate fresh smoke and smoke layers at higher altitudes, respectively [48].…”
Section: Discussionmentioning
confidence: 99%
“…In theory, if particles are perfectly spherical, no backscattering in the perpendicular, or orthogonal plane, should occur. This means irregularly shaped particles cause perpendicular backscattering [7] [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of fluorescent ambient aerosol was reported for the first time using a LIDAR system (Immler et al, 2005), attributing the signals to a combination of PAH-containing particles and/or PBAP. Furthermore, it was shown (Sassen, 2008) that pollen can generate strong laser depolarisation in LIDAR backscatter during Alaskan springtime measurements and suggested that pollen plumes may be mistaken for upper cirrus clouds and therefore introduce important errors into identifying aerosols in the atmosphere. Atmospheric optical phenomena caused by pollen also have been reported, 6 and will be discussed briefly in Section 5.…”
Section: Light Detection and Ranging (Lidar) And Remote Sensingmentioning
confidence: 99%
“…The PDR profile in Berlin showed a maximum in the lowest visible layer and decreased regularly with altitude throughout the PBL. The particularly large amount of pollens reported this day might explain this profile: pollens are very coarse particles that are too heavy to reach the upper levels of the PBL, but have a high depolarizing power [55,56]. This combined with the effect of relative humidity, as aerosols reaching the upper levels of the PBL became less depolarizing due to water-coating.…”
Section: Berlinmentioning
confidence: 99%